(untitled) (Publicaciones en Ciencias y Tecnología, 2009)
The problem of caculating eingenvalues has taken more importance, due to growing num- ber of applications involving matrices that represents several real system. In specific ap- plications as flow mechanics, the interest is gettings an extreme eingenvalues; so the op- timization approach emerge as a relevant option. In this work the utility of calculating generalized eingenvalues in the resulting matix from a discrete equation coming from a real applications, is described as an optimization problem. A polynomial type objective function proposed by Auchmuty is used.